Differential Hypermethylation of Death-Associated Protein Kinase Promoter in Central Neurocytoma and Oligodendroglioma. (27th April 2014) - Chung, Chia-Li; Tsai, Hung Pei; Tsai, Cheng-Yu; Chen, Wan-Tzu; Lieu, Ann-Shung; Wang, Chih-Jen; Sheehan, Jason; Chai, Chee-Yin; Kwan, Aij-Lie
Abstract : Background . Central neurocytoma and oligodendroglioma are rare tumors of the central nervous system. However, diagnosis between these two types of tumors is challenging due to their many cytological and histological similarities. Death-associated protein kinase (DAPK) is a calcium/calmodulin-regulated serine/threonine protein kinase involved in many apoptosis pathways, and repressed expression of DAPK by promoter hypermethylation has been found in a variety of human cancers. The purpose of this study was to assess DAPK protein expression and promoter hypermethylation in central neurocytoma and oligodendroglioma. Method . Central neurocytoma and oligodendroglioma samples were obtained from age- and sex-matched patients. DAPK protein expression was performed using immunohistochemical assays in formalin-fixed, paraffin-embedded sections. DAPK promoter hypermethylation was carried out using bisulfite-modified genomic DNA in methylation-specific PCR followed by separation in agarose gels. Findings . A statistically significant difference (P = 0.021 ) in DAPK promoter hypermethylation between central neurocytoma (76.9%) and oligodendroglioma (20%) was observed. High levels of DAPK protein expression were generally found in oligodendroglioma (90%), compared with 38.5% in central neurocytoma (P = 0.054 ; not statistically significant). There was an inverse correlation between DAPK protein expression and DAPK promoter hypermethylation in the cohort of 23 patients (P = 0 .002 ). Conclusions . The results show that DAPK promoter hypermethylation and repressed expression of DAPK protein were more common in central neurocytoma than in oligodendroglioma. Thus, DAPK promoter hypermethylation could be useful for differential diagnosis between these two types of tumors, whereas DAPK protein expression might be less predictive. The role of DAPK promoter hypermethylation in the pathogenesis of central neurocytoma warrants further study.